Anthropological analysis of early medieval population from Milicz (12th - 13th c.) - Miszkiewicz, Brunon; Gronkiewicz, Stanisław (Anthropological Review, 1986)
The investigated population originates from an area with a particularly intensive colonization. With the help of typological analysis the authors try to find ethnogenic connections of the population of Milicz.